The Role of the Ministry of Industry as the Main Stakeholder in the Development of IKM Centers in Indonesia - Amirullah Amirullah; Asep Jubaedillah; M. Zidane Qadafi Lubis; Faria Ruhana (Publikasi Indonesia, 2024)
Small and medium industries (SMEs) are vital sectors in Indonesia's economy, with significant contributions to Gross Domestic Product (GDP) and job creation. The IKM Center, which groups small and medium-sized business units in one location, is expected to improve production efficiency and industrial competitiveness. However, many centers are experiencing problems in management and revitalization. This research aims to explore the role of the Ministry of Industry as the main stakeholder in the development of IKM Centers in Indonesia. Using a descriptive qualitative approach, this study examines the role of the Ministry of Industry as a regulator, facilitator, catalyst, investor, and strategic planner in developing SME Centers. The results of the study show that although the IKM Center has great potential, there are still challenges in policy implementation and management that require revitalization. The government is expected to continue to strengthen its role to support the sustainability and growth of the IKM Center in the long term